GE_GERICHTE C/11196/2012 vom 2. Dezember 2013 - GE Cour de justice (2013)
RÉSILIATION; FORME ÉCRITE; HEURES DE TRAVAIL SUPPLÉMENTAIRES | CPC.317.1; CO.334.1; CO.334.2; CO.335.1; CO.321c.1; CO.330a.1; CO.322.1; CO.324.1; CO.16.1; LACI.29.2